Effectiveness of low-level laser therapy in patients with maxillofacial neuropathies. A systematic review of randomized controlled trials - Leonardo Díaz; Javier Basualdo; Alain Chaple-Gil; Alfredo Von Marttens; Eduardo Fernández (Photodiagnosis and Photodynamic Therapy, 2025)
Objective: This study aimed to evaluate the effectiveness and safety of low-level laser therapy (LLLT) in managing maxillofacial neuropathies, with a focus on pain reduction, neurological recovery, and tissue regeneration. Methods: A systematic search of PubMed, Web of Science, Scopus, and EBSCO databases was conducted for English-, Spanish-, and Portuguese-language publications on LLLT for maxillofacial neuropathies up to December 2024. Randomized controlled trials (RCTs) involving patients with paresthesia, neuralgia, or facial paralysis treated with LLLT were included. Data extraction and risk-of-bias assessments were conducted by two independent reviewers, and results were synthesized qualitatively and quantitatively. Results: From an initial pool of 841 studies, 18 RCTs involving 1,220 patients met the inclusion criteria. LLLT significantly reduced pain scores on the Visual Analog Scale (VAS) (mean reduction = –3.5, 95 % CI:4.2 to –2.8, P < 0.001) and facilitated a 45 % faster recovery of sensory thresholds compared to controls (P < 0.001). Tissue regeneration markers, including collagen deposition and epithelialization rates, improved, resulting in a 25 % reduction in healing times (P < 0.05). Mild adverse events, such as transient erythema, were reported in <5 % of cases. Variability in laser dosimetry and small sample sizes across studies were noted. Conclusion: Low-level laser therapy is an effective and safe modality for managing maxillofacial neuropathies, demonstrating significant benefits in pain reduction, nerve recovery, and tissue healing. Standardized protocols and multicenter trials are necessary to optimize its application.